(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Cancer remains one of the leading causes of morbidity and mortality worldwide, presenting a significant challenge to public health. The treatment of cancer requires a multidisciplinary approach, with medicine playing a crucial role. This article provides a comprehensive overview of the role of medicine in the treatment of cancer, focusing on the various modalities and advancements in medical interventions. It discusses the use of chemotherapy, targeted therapy, immunotherapy, and hormone therapy, highlighting their mechanisms of action and clinical applications. Additionally, the article explores the role of supportive care in managing cancer-related symptoms and improving patients’ quality of life. Overall, this article emphasizes the importance of integrating medicine into the holistic care of cancer patients to achieve optimal outcomes.